Analysing ICT Integration Tools in Tanzanian Early Childhood Education: Policy, Constraints, and Frameworks - Beatus B. Mapunda (Asian Journal of Early Childhood and Elementary Education, 2026)
The integration of Information and Communication Technology (ICT) into Early Childhood Education (ECE) has received increasing global attention; however, research on the suitability of standardised tools for evaluating ICT integration in Tanzanian ECE remains limited. This study aims to critically examine existing standardised evaluation tools and develop a contextualised framework appropriate for Tanzania’s resource-constrained educational environment. A critical literature review design was employed, drawing on policy documents, national education statistics, teacher education curriculum documents, international frameworks, and scholarly literature addressing ECE quality, digital pedagogy, teacher competence, and ICT integration. The reviewed sources were analysed using thematic content analysis. The findings indicate that no single standardised instrument adequately captures the multidimensional nature of ICT integration in Tanzanian pre-primary education. Existing tools, including child-outcome instruments such as MELQO and IDELA; classroom-process tools such as Teach ECE, CLASS, and ECERS-3; teacher-competence frameworks such as UNESCO ICT-CFT and UNICEF digital competence frameworks; and system-readiness indicators each assess important but partial dimensions of ICT integration. The review further demonstrates that meaningful ICT integration depends on the interaction among infrastructure readiness, teacher digital capability, pedagogical mediation, and children’s learning opportunities and outcomes. This study contributes to the literature by proposing a contextualised ecological-capability framework that integrates these dimensions within a unified analytical model. It concludes that evaluating ICT integration in Tanzanian ECE requires a layered, multidimensional, and context-sensitive approach rather than reliance on individual instruments. The proposed framework provides practical implications for policymakers, teacher educators, and researchers by offering a more comprehensive basis for assessing digital integration in resource-constrained pre-primary settings, while also highlighting the need for future empirical validation across diverse educational contexts in Tanzania.